QstR-dependent regulation of natural competence and type VI secretion in Vibrio cholerae. Issue 20 (8th August 2018) - Jaskólska, Milena; Stutzmann, Sandrine; Stoudmann, Candice; Blokesch, Melanie
Abstract: During growth on chitinous surfaces in its natural aquatic environment Vibrio cholerae develops natural competence for transformation and kills neighboring non-immune bacteria using a type VI secretion system (T6SS). Activation of these two phenotypes requires the chitin-induced regulator TfoX, but also integrates signals from quorum sensing via the intermediate regulator QstR, which belongs to the LuxR-type family of regulators. Here, we define the QstR regulon using RNA sequencing. Moreover, by mapping QstR binding sites using chromatin immunoprecipitation coupled with deep sequencing we demonstrate that QstR is a transcription factor that binds upstream of the up- and down-regulated genes. Like other LuxR-type family transcriptional regulators we show that QstR function is dependent on dimerization. However, in contrast to the well-studied LuxR-type biofilm regulator VpsT of V. cholerae, which requires the second messenger c-di-GMP, we show that QstR dimerization and function is c-di-GMP independent. Surprisingly, although ComEA, which is a periplasmic DNA-binding protein essential for transformation, is produced in a QstR-dependent manner, QstR-binding was not detected upstream of comEA suggesting the existence of a further regulatory pathway. Overall, these results provide detailed insights into the function of a key regulator of natural competence and type VI secretion in V. cholerae .